Defamiliarization in Ibn Hisham’s Interpretation of The Poem, Banat Souad by Kaeb bin Zuhair - Ghayath Babo (دراسات في اللغة العربيّة وآدابها)
This study provides a new textual interpretation of the poem, Banat Souad by Kaeb bin Zuhair. This study emphasizes defamiliarization, which Kaeb has employed in his poem, technique which produces artistic and ideational richness. This defamliarization has taken place at both morphological and syntactic levels. In his commentary on the poem, Ibn Hisham Ansari, used the same patterns and revealed its hidden meanings. The present study shows Ibn Hisham’s ability in semantics and points out his multiple interpretations of the same lines of poetry. In this article, we have tried to show the relation between syntax and semantics. Deviation from the textual mainstream is for rhetorical and expressive purposes and the poet employs it show one surprising way of expression. This deviation from the linguistic norms enlivens the language, helps its development and progress, and brings about creative constructions.